2017
DOI: 10.3892/ol.2017.7265
|View full text |Cite
|
Sign up to set email alerts
|

Screening of up‑ and downregulation of circRNAs in HBV‑related hepatocellular carcinoma by microarray

Abstract: Abstract. The present study describes circular RNA (circRNA) profiles in three pairs of hepatocellular carcinoma (HCC) tissues and the corresponding adjacent non-tumorous tissues (NTs) by microarray. circRNA is a type of endogenous RNA that serve a crucial role in disease development and aberrantly express in a number of types of cancer. In the present study, 3 paired HCC tissues and paired adjacent NTs were collected from HCC surgical specimens from 3 hepatitis B virus-infected patients with HCC. With abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 54 publications
(35 reference statements)
1
26
0
Order By: Relevance
“…Lastly, the regulatory axes of circRNAs, miRNAs, and mRNAs are gradually demonstrated in different kinds of diseases [10][11][12], including HCC [6,8]. According to previous studies, a huge number of ncRNAs, including circRNAs and miRNAs, are dysregulated in HCC [12][13][14]. In the present study, we downloaded two microarray analysis results (GSE78520 and GSE43445) and found that a total of 13 circRNAs upregulated in HCC tumor tissues obtained a foldchange > 3.0, and a total of 142 miRNAs were differentially expressed in HCC tissues with metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Lastly, the regulatory axes of circRNAs, miRNAs, and mRNAs are gradually demonstrated in different kinds of diseases [10][11][12], including HCC [6,8]. According to previous studies, a huge number of ncRNAs, including circRNAs and miRNAs, are dysregulated in HCC [12][13][14]. In the present study, we downloaded two microarray analysis results (GSE78520 and GSE43445) and found that a total of 13 circRNAs upregulated in HCC tumor tissues obtained a foldchange > 3.0, and a total of 142 miRNAs were differentially expressed in HCC tissues with metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…However, the expression profiles and functions of circRNAs during viral infection remain largely unknown. To date, there have only been quite a few reports regarding the identification and characterization of circular RNAs during the infection of ebola virus, hepatitis B virus, avian leukosis virus subgroup-J and DNA tumor virus SV40 (Cui et al, 2018;Shi et al, 2017;Wang et al, 2017;Zhang et al, 2017). There is still a long way to elucidate the detailed functions and mechanism of circRNAs in viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs possess miRNA-sponging activity and counteract the miRNA's inhibitory activity on the target mRNA [6,7]. Recent studies showed that the expressions of circRNAs were perturbed in viral infections caused by both DNA (hepatitis B virus, Kaposi's sarcomaassociated herpesvirus, and simian vacuolating virus 40) and RNA [Ebola virus, porcine epidemic diarrhea virus (PEDV), transmissible gastroenteritis virus (TGEV), influenza A viruses, and avian leukosis virus subgroup-J] viruses [8][9][10][11][12][13][14][15], and that these cir-cRNAs might serve as potential antiviral targets [9,12,16].…”
Section: Introductionmentioning
confidence: 99%